Clear Cell Carcinoma of the Endometrium Causing Paraneoplastic Retinopathy: Case Report and Review of the Literature - Paulina Cybulska; Eduardo V. Navajas; Filiberto Altomare; Marcus Q. Bernardini (Case Reports in Obstetrics and Gynecology)
We reviewed the literature for cases in which gynecologic malignancies caused paraneoplastic retinopathy and ultimately led to blindness. Twenty-eight cases were derived from the literature, and one unique case is described from our institution. Of these 28 cases, 14 patients were diagnosed with endometrial cancer, 7 with ovarian cancer, 5 with cervical cancer, 1 fallopian tube cancer and 1 with concomitant endometrial and ovarian cancers. The average age of patients at the time of diagnosis was 64 years (range, 35–89 years). Typically, ocular manifestations antedate symptoms of the underlying carcinoma by 3–12 months. Information regarding the interval from visual symptoms to time of death is limited, but ranges from several months to several years. Our report is the first to document a clear cell carcinoma of the endometrium causing paraneoplastic retinopathy and is the first to review all gynecologic malignancies associated with visual paraneoplastic syndromes.